Implementasi Kurikulum Untuk Meningkatkan Karakter Siswa - Manalu, Rony Ismail; Siregar, Samsuddin; Girsang, Rio Daska; Barus, Elyezer Agustinus (JPKO Jurnal Pendidikan dan Kepelatihan Olahraga, 2024)
Along with rapid social, cultural, work world changes, and technological advances, the Ministry of Education and Culture (KEMENDIKBUD) designed the Independent Curriculum to prepare students to face future challenges. This curriculum encourages creative, innovative, and relevant learning processes, as well as developing aspects of attitudes, knowledge, and skills. This study aims to examine the implementation of the curriculum to improve student character, the 2013 Curriculum (K13) with the Independent Curriculum and examine the implementation of the Independent Curriculum at SD Negeri 173308 Sibaragas in our study, namely the Implementation of the Curriculum to Improve Student Character. The research method used is qualitative, with an in-depth focus on the learning process and experience. The results of the study show that the K13 RPP has a more formal structure with 13 components, while the Independent Curriculum is more flexible, allowing teachers to adjust learning to student needs. The implementation of the Independent Curriculum at SD Negeri 173308 Sibaragas improves students' skills and independence in learning because students have good character in school and outside of school.